An Approach of Resource Allocation for Vehicle-to-Vehicle Communication using Cuckoo Search based Grey Wolf Optimization - Sadashiviah, Sheela; Ramaswamy, Nataraj Kanathur (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Vehicles in networks can experience rapid channel changes due to their high mobility, which can greatly affect the effectiveness of resource allocation methods. Hence, it is crucial to consider these variations in developing resource allocation techniques for D2D-enabled vehicular networks. To address this issue, this study suggests a CS-GWO based method for power allocation and spectrum sharing, which is optimized for enhancing the performance of V2I and V2V connections, and is also resistant to channel variations. The suggested algorithms aim to maximize the ergodic capacity of V2I links while assuring dependable performance for each V2V connection. This research could prove beneficial in developing future vehicular communication systems.